The comparison of intrapartum sonographic signs and digital examination in fetus with cephalic presentation - Rachaya Moonsri (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2020. Objective: The agreement of fetal head position examined by digital vaginal examination (DVE) and intrapartum sonographic signs (ISS) in pregnant women during labor. Materials and Methods: A cross-sectional study was conducted. Two hundred eight-term singleton pregnant women attending labor at Ramathibodi Hospital, Thailand with the fetal cephalic presentation, cervical dilatation of 4 to 8 cm, station -2 or below and no contraindication for DVE were enrolled. The DVE evaluating fetal head position was performed by the third-year obstetrical residents. After DVE, ISS via transabdominal ultrasound for determining fetal head position was obtained immediately by the first researcher. The DVE report and the ultrasonographic images of ISS were recorded separately. The fetal head position based on ISS was designated by the second researcher blinded to the DVE result. The agreement of DVE and ISS for determining fetal head position was analyzed. Results: Two hundred eight pregnant women were analyzed. The fetal head position detected by DVE was consistent with that of ISS at 41.3% (p<0.001). The most percent agreement was observed in the fetus with left occiput anterior position at 72.7% (p<0.001). The lowest percent agreement was found in the direct occiput posterior at 14.3% (p=0.243). Parity, gestational age, current body mass index, epidural analgesia, cervical effacement, caput succedaneum, molding, and station did not significantly affect the discrepancy between DVE and ISS. Conclusion: The agreement between DVE and ISS for evaluating the fetal head position was low. The ISS might be considered for evaluating the fetal head position.